The relationship between physical activity behavior and cardiovascular health among university employees - Hsieh, Hsien (My University, 2018)
PURPOSE: The purpose of this study was to evaluate the relationship between physical activity behavior and cardiovascular health among university employees (N = 30). In addition, the research also attempted to explore and explain potential underlying barriers to being physically active. METHODS: Healthy university employees from 30-65 years of age were recruited for this study and the following data was collected – physical activity rating, blood pressure, BMI, and waist circumference. A non-exercise fitness test was conducted to predict VO2 max. The Pearson correlation coefficient was used to test the correlation between physical activity behavior and several cardiovascular disease (CVD) risk factors. RESULTS: The research data indicated that various CVD risk factors were found, including sedentary lifestyle (83%), hypertension (67%), overweight or obesity (50%), central obesity (40%) and poor VO2 max (77%). A significant correlation was found between physical activity behavior and excess body fat (r = 0.89), hypertension (r = 0.599; P < 0.01), central obesity (r = 0.365; P < 0.05) and poor VO2 max (r = 0.539; P < 0.01). In addition, the lack of time was the most common barrier to being physically active. CONCLUSION: The results showed a severe phenomenon for a high risk of CVD among university employees. Occupational sedentary behavior accounted for the high risk of CVD, which resulted from poor self-efficacy. Exercise interventions were confirmed to be effective to improve self-efficacy. Future research should employ randomized controlled trials, larger sample sizes, and physical activity counseling to strengthen intervention effects in order to promote physical activity and prevent occupational sedentary behavior.
Thesis, M.S., Clinical Exercise Physiology, UWRF, 2018.